Sharia Compliance and Economic Efficiency in Minangkabau Traditional Sharecropping - Endrizal Ridwan; Inneke Herti Vania (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2023)
Islamic financing contracts currently marketed in Indonesia use Arabic terminology that might sound strange to many Indonesian Muslims. Even though these financing contracts comply with the sharia components, they may be inefficient in the context of local wisdom. This paper identifies traditional contracts that are potentially modified to become sharia compliance. We analyzed the traditionally practiced business contracts of sharecropping in Minangkabau West Sumatra and tested whether the contracts fulfilled sharia compliance and economic efficiency. We interviewed seventy practicing sharecroppers and fourteen local leaders and clerks to seek their perceptions about two types of Minangkabau traditional contracts of paduo and patigo, regarding economic efficiency, fairness, and sharia compliance. We found that the respondents in general believed that the practiced sharecropping contracts fulfilled most of the sharia requirements. However, the need for the written agreement, presence of witnesses, and definite duration were unsatisfactory to avoid gharar. The majority of respondents believed that the contracts were fair but inefficient. Modification of contracts in terms of proper legal drafting, presence of witnesses, and finite duration is necessary. The modified contracts will be beneficial to support the emergence of formal Islamic financial institutions which are culturally compatible.